Decolonizing Description: First Steps to Cataloguing with Indigenous Syllabics - Fagnan, Luc (University of Alberta Library, 2020)
In light of the TRC Calls to Action from 2015 and the CFLA’s Truth & Reconciliation Report and Recommendations from 2017, many libraries in what is known as Canada have begun to take steps towards decolonization. Decolonizing bibliographic descriptions in library catalogues is an important part of this process, as this can impact both the ability to access Indigenous materials and the representation of Indigenous Peoples and Knowledges in the library. While various efforts to work towards accurately and respectfully representing Indigenous Peoples and Knowledges in library catalogues are ongoing, the inclusion of Indigenous Syllabics in bibliographic records is one way in which cataloguers can begin to put these efforts into action. In addition to collaborating with Indigenous community members and Indigenous librarians on this work, there are a variety of resources and tools available online that can aid cataloguers in creating accurate and culturally appropriate descriptions of Indigenous materials. This extended abstract provides context and information that is central to this work, and gives a cursory overview of how one might insert Indigenous Syllabics into bibliographic records.